System of exercises for development of students’ motor abilities - Nikolay L. Ponomarev, Anatoly A. Opletin, Aleksandr N. Legotkin, Valery D. Panachev, Leonid A. Zelenin, (Opción, 2019)
The article presents empirical research analysis and provides recommendations on the development of students’ coordination abilities in physical education classes aimed at solving innovative problems all the generations face in the new millennium. The results of the ascertaining experiment prove the identity of physical fitness and coordination abilities of students in the control and experimental groups. In conclusion, Coordination of movements with closed eyes, CAc and CApc, confirmed a high level of improvement in the development of sensory (sensitive) and precise motor functions in students of the experimental group.